Estimating the Effect of an Increase in the Minimum Wage on Hours Worked and Employment in Ireland - Seamus McGuinness; Paul Redmond (Institute of Labor Economics (IZA), 2018)
On the 1st of January 2016 the Irish National Minimum Wage increased from exteuro8.65 to exteuro9.15 per hour, an increase of approximately six percent. We use a difference-in-differences estimator to evaluate whether the change in the minimum wage affected the hours worked and likelihood of job loss of minimum wage workers. The results indicate that the increase in the minimum wage had a negative and statistically significant effect on the hours worked of minimum wage workers, with an average reduction of approximately 0.5 hours per week. The effect on minimum wage workers on temporary contracts was higher at 3 hours per week. We found a corresponding increase in part-time employment of 2 percentage points for all minimum wage workers and 10 percentage points for those on temporary contracts. We find no clear evidence that the increase in the minimum wage led to an in-creased probability of becoming unemployed or inactive in the six-month period following the rate change.
Keywords: E24; J22; J23; J31; J42; 330; minimum wage; hours of work; employment; unemployment